2007
DOI: 10.1161/01.res.0000260181.19449.95
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations of Vascular Homeostasis and Aortic Valve Abnormalities in Fibulin-4 Deficient Mice

Abstract: Abstract-The Fibulins are a 6-member protein family hypothesized to function as intermolecular bridges that stabilize the organization of extracellular matrix structures. Here, we show that reduced expression of Fibulin-4 leads to aneurysm formation, dissection of the aortic wall and cardiac abnormalities. Fibulin-4 knockdown mice with a hypomorphic expression allele arose from targeted disruption of the adjacent Mus81 endonuclease gene. Mice homozygous for the Fibulin-4 reduced expression allele (Fibulin-4 R/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
164
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(179 citation statements)
references
References 24 publications
15
164
0
Order By: Relevance
“…Thus, in MAGP-1-null mice (Weinbaum et al, 2008), lack of competition for LLC binding to microfibrils could result in enhanced microfibril-bound LLC and reduced active TGF. By contrast, enhanced TGF activity in mice depleted of fibulin-4 (Hanada et al, 2007) suggests a stabilizing role for fibulin-4, which is consistent with our finding that, unlike MAGP-1, exogenous fibulin-4 does not release TGF from microfibrils. We have also shown that fibulin-4 can strongly bind LTBP-1, and can simultaneously bind LTBP-1 and fibrillin-1, implicating fibulin-4 as a key mediator in the association of LTBP-1 with microfibrils (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Thus, in MAGP-1-null mice (Weinbaum et al, 2008), lack of competition for LLC binding to microfibrils could result in enhanced microfibril-bound LLC and reduced active TGF. By contrast, enhanced TGF activity in mice depleted of fibulin-4 (Hanada et al, 2007) suggests a stabilizing role for fibulin-4, which is consistent with our finding that, unlike MAGP-1, exogenous fibulin-4 does not release TGF from microfibrils. We have also shown that fibulin-4 can strongly bind LTBP-1, and can simultaneously bind LTBP-1 and fibrillin-1, implicating fibulin-4 as a key mediator in the association of LTBP-1 with microfibrils (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Fibulin-4 binds strongly to full-length LTBP-1 and fibrillin-1 Fibulin-4 binds fibrillin-1 (Choudhury et al, 2009;Ono et al, 2009) and colocalizes with microfibrils (Kobayashi et al, 2007), and fibulin-4 hypomorphic mice have enhanced TGF activity (Hanada et al, 2007). Here, BIAcore analysis revealed that fulllength LTBP-1 bound strongly to immobilized full-length fibulin-4 (K D 2.1±0.12 nM) (Fig.…”
Section: Fibrillin Regulates Ltbp-1 Depositionmentioning
confidence: 54%
See 1 more Smart Citation
“…Although the onset of aortic valve stenosis has been reported in Smad6-deficient mice (14), in fibulin 4-deficient mice (15), and in humans with the NOTCH1 mutation (16), the abnormality has primarily been observed during cardiac valve development. As avascular tissues, the cardiac valve complex and cartilage share common structural properties (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Using a mouse model of thoracic aortic disease, the FBLN4 hypomorphic mouse, they found that miR-29a, miR-29b, and miR-29c were increased in aortic aneurysms in the mutant mouse. Aortic disease in the FBLN4 mouse model is associated with evidence of increased TGF-b signaling, including increased nuclear phosphorylated Smad2 (pSmad2) and increased connective tissue growth factor (CTGF) and collagen deposition in the medial and adventitial layer (22). Therefore, it is surprising that miR-29b would be increased rather than decreased in the diseased aorta.…”
Section: Aortic Aneurysms and Mir-29bmentioning
confidence: 99%